1993
DOI: 10.1085/jgp.101.4.545
|View full text |Cite
|
Sign up to set email alerts
|

Trinitrophenyl-ATP blocks colonic Cl- channels in planar phospholipid bilayers. Evidence for two nucleotide binding sites.

Abstract: Outwardly rectifying 30-50-pS C1-channels mediate cell volume regulation and transepithelial transport. Several recent reports indicate that rectifying CI-channels are blocked after addition of ATP to the extracellular bath (Alton, E. W. 356:238-241). Therefore, we decided to conduct a more detailed study of the ATP binding site using a higher affinity probe. We tested the ATP derivative, 2',3',0-(2,4,6-trinitrocyclohexadienylidene) adenosine 5'-triphosphate (TNP-ATP), which has a high affinity for certain nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A putative nucleotide binding site is located in the area of the outer mouth of the predicted pore. In fact, mutating this binding region from GxGxG to AxGxG or AxAxA (G = gly cine; A = alanine; x = different amino acids) dramatically reduces the ability of cAMP to block Itm-Nucleotide-sensitive chloride chan nels have also been found in tracheal epithelia [9], cardiac cells after swelling [10] and colonic chloride channels reconstituted in planar phospholipid bilayers [11], In contrast to the wild type In", the AxAxA mutant was highly sensitive to extracellular calcium concentration showing a dramatic de crease of the current amplitude in the nominal absence of calcium in the extracellular fluid (omitting calcium and adding 1 nuWEGTA). Furthermore, the kinetics of activation were characteristically changed: whereas the kinet ics of the wild type In,, comprised a fast activa tion followed by a slow inactivation at holding potentials more positive than +40 mV, the mutant current showed an initial fast activa tion followed by a further activation not sat urated after 800 ms.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…A putative nucleotide binding site is located in the area of the outer mouth of the predicted pore. In fact, mutating this binding region from GxGxG to AxGxG or AxAxA (G = gly cine; A = alanine; x = different amino acids) dramatically reduces the ability of cAMP to block Itm-Nucleotide-sensitive chloride chan nels have also been found in tracheal epithelia [9], cardiac cells after swelling [10] and colonic chloride channels reconstituted in planar phospholipid bilayers [11], In contrast to the wild type In", the AxAxA mutant was highly sensitive to extracellular calcium concentration showing a dramatic de crease of the current amplitude in the nominal absence of calcium in the extracellular fluid (omitting calcium and adding 1 nuWEGTA). Furthermore, the kinetics of activation were characteristically changed: whereas the kinet ics of the wild type In,, comprised a fast activa tion followed by a slow inactivation at holding potentials more positive than +40 mV, the mutant current showed an initial fast activa tion followed by a further activation not sat urated after 800 ms.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…In a later abstract, this group reported that luminal ATP induces K + secretion via a P2Y 2 receptor in rat distal colonic mucosa [385]. It is interesting that TNP-ATP, which has since been identified as a potent antagonist at P2X1 and P2X3 receptors [686], was shown to block colonic Cl − channels [682], although there do not appear to be reports of the effects of TNP-ATP on P2Y receptors. In situ hybridisation studies have shown that the mRNA for P2X4 receptors is localised in rat intestinal crypts [653].…”
Section: Intestinal Secretionmentioning
confidence: 99%
“…First, we measured the mean amplitude of control (icontr.) and fast-blocked channels (Oblo,k) from amplitude histograms as described previously (Venglarik et al, 1993b). The ratio of iblock'icontrol is related to the underlying change in P.…”
Section: Kinetic Analysismentioning
confidence: 99%